Salicyclic acid against the disruptive effects of cadmium induces oxidative stress and ‎biochemical and histopathological changes in the ovary of the freshwater leech Limnatis ‎nilotica (Savigny, 1822)‎. Issue 1 (31st December 2022) - Khaled, Ichrak; Ahmed, Raja Ben; Saidi, Issam; Abbassi, Raoudha; Abdelkader, Mohamed Omar; Harrath, Abdel Halim
ABSTRACT: In this study, we investigated the effect of Cd on the ovaries of the freshwater leech Limnatis nilotica and the ability of salicylic acid (SA) treatment to alleviate the Cd harmful effects. Our results showed that Cd treatment increased the level of oxidative stress leading to severe alterations in histopathological and biochemical indexes. Cd exposure was found to induce a substantial increase in malondialdehyde (MDA) and hydrogen peroxidase (H2O2) contents as well as an impairment in catalase (CAT) and Glutathione peroxidase (GPx) activities. These findings are thoroughly supported by histopathological evidence which showed several modifications in the ovary cord organization. However, SA addition reduced the toxic effect of Cd-exposure through decreasing MDA and H2O2 levels, the regulation of enzymatic and nonenzymatic antioxidant mechanism pathways leading to the alleviation of the histopathological lesions. These results suggest that SA can prevent damage under Cd toxicity in the leech ovaries.